Investigating the effects of combined treatment of mesalazine with Lactobacillus casei in the experimental model of ulcerative colitis - Bahrami, Shabnam; Babaei, Nahid; Esmaeili Gouvarchin Ghaleh, Hadi; Mohajeri Borazjani, Jaleh; Farzanehpour, Mahdieh (Frontiers in Molecular Biosciences, 2024)
Ulcerative colitis (UC), a common gastrointestinal disorder in affluent nations, involves chronic intestinal mucosal inflammation. This research investigated the effects of combined probiotic treatment of Lactobacillus casei (L. casei) and mesalazine on disease activity index and inflammatory factors in the UC model. 20 male BALB/c mice were utilized and divided into four groups. To induce UC, all groups received 100 μl of 4% acetic acid (AA) intra-rectally. The first group received phosphate-buffered saline (PBS) (as a positive control), the second group was treated with L. casei, the third group was treated with mesalazine and, the fourth group was treated with L. casei and mesalazine. Treatment with L. Casei and mesalazine commenced after the manifestation of symptoms resulting from UC induction. Finally, the mice were euthanized and the disease activity index, myeloperoxidase activity, nitric oxide rate, cytokines level (IL-1β, IL-6, TNF-α) and, gene expression (iNOS, COX-2, and cytokines) were evaluated.The combined treatment of L. casei and mesalazine led to a significant decrease in the levels of NO, MPO and inflammatory cytokines. In addition, the expression of cytokines, iNOS and COX-2 genes decreased in mice treated with the combination.This study shows that combined treatment of L. casei and mesalazine improves of experimental UC, which can be attributed to the anti-inflammatory properties of L. casei and mesalazine. In conclusion, this combination therapy can be considered a suitable option for the management of UC.